Catalyst for hydrogen chloride catalytic oxidation to produce chlorine gas, and preparation method and application thereof

CN118106020BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211523478.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2026-10-30
Estimated Expiration
2042-11-30

AI Technical Summary

Benefits of technology

[0041](1)本发明提供了一种全新的氯化氢催化氧化制氯气催化剂,通过分子筛具有阳离子可交换特性及其本身赋予的三维立体“孔笼”结构,将各催化活性组分通过交换、浸渍方式引入到分子筛孔道内,并占据一定的孔笼可交换位点。通过八面体沸石独特的孔笼骨架结构和电子环境对引入活性金属组分离子形成一定限域效应,同时利用分子筛骨架与交换活性组分金属阳离子之间具有强相互作用,从而提高活性组分在载体上的分散稳定性并与载体紧密结合,有效抑制中心活性组分的流失。将催化活性组分有效分散固定于载体孔道内及表面,得到具有良好分散性稳定性的催化剂的全新思路。由此,基于对催化剂组成结构的特殊设计,使催化剂在使用过程中尽可能保持这种稳定状态,从而有效提高氯化氢催化氧化制氯气催化剂的活性稳定性和延长其使用寿命。本发明提供的催化剂不含有毒成分和贵金属,环境友好制备成本较低,具有良好的工业应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003972227950000011
    Figure BDA0003972227950000011
Patent Text Reader

Abstract

The present application relates to the field of catalyst preparation, and discloses a catalyst for preparing chlorine by catalytic oxidation of hydrogen chloride, a preparation method and application of the catalyst, and a preparation method of chlorine. The catalyst comprises a molecular sieve and an active component supported on the molecular sieve; the active component comprises oxides and / or chlorides of copper, oxides and / or chlorides of an auxiliary metal, oxides and / or chlorides of a rare earth element, and oxides and / or chlorides of an alkali metal; the auxiliary metal is one or more of Group VII B, Group VIII, Group IIB, Group IV B, Group II A and Group V B metals; the content of copper is 1-20 wt% in terms of oxides, the content of the auxiliary metal is 0.1-10 wt%, the content of the rare earth element is 0.1-13 wt%, and the content of the alkali metal is 0.1-10 wt%, relative to the total weight of the catalyst. The catalyst solves the problem of easy volatilization and loss of the metal active center of the catalyst, and can improve the catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst preparation, specifically to a catalyst for the catalytic oxidation of hydrogen chloride to chlorine, its preparation method and application, and a method for preparing chlorine. Background Technology

[0002] Chlorine, as an important basic chemical raw material, is mainly used in the production of chlorine-consuming products such as PVC (polyvinyl chloride), polyurethane intermediates (MDI, TDI, HDI), organofluorine compounds, pesticides, and pharmaceuticals. In the production of organochlorinated products, the utilization rate of chlorine atoms is at most 50%, with the remaining chlorine atoms being converted into hydrogen chloride. Currently, there are two main ways to handle the byproduct hydrogen chloride in industry. One is to use it to prepare hydrochloric acid, which has a higher impurity content and is cheaper; the other is to use it as a raw material for the synthesis of chlorine-containing compounds such as vinyl chloride. However, neither of these pathways can completely consume the byproduct hydrogen chloride, and policies regarding the transportation and emission of toxic and highly corrosive chemicals are becoming increasingly stringent. The disposal and utilization of large quantities of byproduct HCl has become a common problem restricting the development of many chlorine-related industries.

[0003] Therefore, directly converting the large quantities of difficult-to-treat HCl produced as a byproduct in industrial production into chlorine gas for utilization, achieving a closed-loop chlorine cycle and zero emissions in the reaction process, is an essential path to achieving green and sustainable development. Using oxygen or air as an oxidant to oxidize hydrogen chloride to produce chlorine gas is an excellent approach. Its stoichiometric formula can be expressed as:

[0004]

[0005] Domestic and international enterprises and research institutions have conducted extensive research on the secondary utilization of by-product hydrogen chloride. Currently, there are three processes capable of producing chlorine from hydrogen chloride through catalytic oxidation: catalytic oxidation, cyclic oxidation, and oxidative electrolysis. Catalytic oxidation involves oxidizing HCl to chlorine and H2O using oxygen under catalytic conditions. Representative processes include the Deacon process, the Shell process, and Sumitomo's technology. The biggest advantage of this technology is its low energy consumption (approximately 230 kW / ton), making it a green and environmentally friendly chemical process. It also boasts advantages such as strong applicability to HCl feedstock and stable process operation.

[0006] A common drawback of copper-based catalysts for the catalytic oxidation of hydrogen chloride is the low HCl conversion rate and rapid catalyst deactivation. This is mainly due to the requirement of high reaction temperatures, and the fact that the catalytic reaction itself is exothermic. The active component, the reactive metal chloride, namely copper chloride, volatilizes rapidly at high temperatures (above 400°C), leading to a rapid decrease in its activity and stability.

[0007] To address this issue, existing technologies have proposed several solutions, such as co-impregnating the central active metal copper with rare earth elements or alkali metals as auxiliary elements, or using a stepwise impregnation method on a corresponding support to form a high-boiling-point composite salt to improve stability. These existing methods can improve catalytic stability to some extent. However, the distribution of copper and other doped metal elements or auxiliary elements on the support is often amorphous and non-uniform, lacking strong interaction with the support itself. This affects the synergistic effect between the support and the active component, resulting in poor stability. Furthermore, the active metal and auxiliary elements are prone to migration and aggregation after drying and high-temperature calcination, making it difficult to achieve uniform, stable, and highly dispersed components. Summary of the Invention

[0008] The purpose of this invention is to overcome the problems of poor activity and stability of supported copper-based catalysts prepared by traditional methods, and to provide a catalyst with highly dispersed and stable catalytic active components, its preparation method and application, and a method for preparing chlorine. This catalyst solves the problem of easy volatilization and loss of the catalyst's metal active centers, and at the same time can improve catalytic performance.

[0009] To achieve the above objectives, the present invention provides a catalyst for the catalytic oxidation of hydrogen chloride to chlorine, the catalyst comprising a molecular sieve and an active component supported on the molecular sieve;

[0010] The active components include oxides and / or chlorides of copper, oxides and / or chlorides of auxiliary metals, oxides and / or chlorides of rare earth elements, and oxides and / or chlorides of alkali metals.

[0011] The auxiliary metal is one or more metals selected from Group VIIB, Group VIII, Group IIB, Group IVB, Group IIA, and Group VB.

[0012] Relative to the total weight of the catalyst, the content of copper, calculated as oxides, is 1-20 wt%, preferably 5-16 wt%, more preferably 6-14 wt%; the content of auxiliary metals is 0.1-10 wt%, preferably 0.1-5 wt%, more preferably 0.1-1.5 wt%; the content of rare earth elements is 0.1-13 wt%, preferably 3-10 wt%, more preferably 4.5-10 wt%; and the content of alkali metals is 0.1-10 wt%, preferably 1-8 wt%, more preferably 2-5 wt%.

[0013] Preferably, the auxiliary metal is one or more selected from manganese, cobalt, magnesium, zinc, nickel, titanium, vanadium, and chromium.

[0014] Preferably, the rare earth element is one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium.

[0015] Preferably, the alkali metal is sodium and / or potassium.

[0016] Preferably, the molecular sieve is one or more of X-type molecular sieve, Y-type molecular sieve and ZSM-5 type molecular sieve, preferably Y-type molecular sieve, more preferably NaY molecular sieve, ultra-stable Y-type molecular sieve, NH4Y molecular sieve, HY molecular sieve and rare earth-containing Y-type molecular sieve.

[0017] A second aspect of the present invention provides a method for preparing a catalyst for the catalytic oxidation of hydrogen chloride to chlorine, the method comprising the following steps:

[0018] (1) Molecular sieve, binder and extrusion aid are dry mixed, and the resulting mixed powder is mixed with adhesive solvent, water and optional first rare earth element salt and then shaped, and then dried and calcined to obtain shaped molecular sieve.

[0019] (2) The shaped molecular sieve obtained in step (1) is impregnated with a mixed solution containing active components, and then the catalyst is obtained by a second drying and a second calcination.

[0020] The mixed solution containing active components contains copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt.

[0021] The auxiliary metal in the auxiliary metal salt is one or more metals selected from Group VIIB, Group VIII, Group IIB, Group IVB, Group IIA, and Group VB.

[0022] The amounts of the first rare earth element salt, copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt used in the obtained catalyst are such that, relative to the total weight of the catalyst, the content of copper, calculated as oxides, is 1-20 wt%, preferably 5-16 wt%, more preferably 6-14 wt%; the content of the auxiliary metal is 0.1-10 wt%, preferably 0.1-5 wt%, more preferably 0.1-1.5 wt%; the content of the rare earth element is 0.1-13 wt%, preferably 3-10 wt%, more preferably 4.5-10 wt%; and the content of the alkali metal is 0.1-10 wt%, preferably 1-8 wt%, more preferably 2-5 wt%.

[0023] Preferably, the method further includes: contacting the shaped molecular sieve obtained in step (1) with an ammonium acid solution and then performing the impregnation step (2), wherein the ammonium acid solution contains an acid and an ammonium salt.

[0024] Preferably, in the ammonium acid solution, the acid is one or more of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, oxalic acid, and citric acid, and the ammonium salt is one or more of ammonium nitrate, ammonium sulfate, and ammonium chloride.

[0025] Preferably, the auxiliary metal in the auxiliary metal salt is a metal from Group VIIB, Group VIII, Group IIB, Group IIB, Group IIA, or Group VB, and more preferably one or more of manganese, cobalt, magnesium, zinc, nickel, titanium, vanadium, and chromium.

[0026] Preferably, the rare earth element in the rare earth element salt is one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium.

[0027] Preferably, the alkali metal in the alkali metal salt is sodium and / or potassium.

[0028] Preferably, in step (1), the molecular sieve is one or more of X-type molecular sieve, Y-type molecular sieve and ZSM-5 type molecular sieve, preferably Y-type molecular sieve, more preferably NaY molecular sieve, ultra-stable Y-type molecular sieve, NH4Y molecular sieve, HY molecular sieve and rare earth-containing Y-type molecular sieve.

[0029] Preferably, in step (1), the dry mixing time is 20 minutes or more.

[0030] Preferably, in step (1), the gel solvent solution is one or more of nitric acid, hydrochloric acid, and phosphoric acid, with a preferred concentration of 0.1-65 wt%.

[0031] Preferably, in step (1), the kneading time for molding is preferably 30-180 min, more preferably 30-120 min.

[0032] Preferably, in step (1), the first roasting temperature is 400-650℃ and the roasting time is 1-6h.

[0033] Preferably, in step (2), the impregnation is atmospheric pressure impregnation or vacuum impregnation at 0-99°C, preferably vacuum impregnation, and the impregnation time is 0.1-12h.

[0034] Preferably, in step (2), the second drying temperature is 60-120℃, more preferably 80-110℃, and the drying time is 2-12h, more preferably 6-12h.

[0035] Preferably, in step (2), the conditions for the second calcination include: under an oxygen-containing atmosphere, the calcination temperature is 400-600℃, preferably 450-550℃, and the calcination time is 2-8h, preferably 4-6h.

[0036] A third aspect of the present invention provides the application of the catalyst of the present invention described above, or the catalyst obtained by the preparation method of the present invention described above, in the catalytic oxidation of hydrogen chloride to produce chlorine.

[0037] A fourth aspect of the present invention provides a method for preparing chlorine gas, the method comprising: contacting hydrogen chloride with oxygen in the presence of a catalyst;

[0038] The catalyst is either the catalyst of the present invention described above or a catalyst obtained by the preparation method of the present invention described above.

[0039] Preferably, the conditions for the contact reaction include: a temperature of 350-390°C, a pressure of 0-0.5 MPa, and a molar ratio of hydrogen chloride to oxygen of 8-0.5:1.

[0040] Compared with existing technologies, the above technical solution has the following advantages:

[0041] (1) This invention provides a novel catalyst for the catalytic oxidation of hydrogen chloride to chlorine. Utilizing the cation exchangeability of molecular sieves and their inherent three-dimensional "porous cage" structure, various catalytically active components are introduced into the pores of the molecular sieve through exchange and impregnation, occupying specific exchangeable sites. The unique pore-cage framework structure and electronic environment of the octahedral zeolite create a confinement effect on the introduced active metal ions. Simultaneously, the strong interaction between the molecular sieve framework and the exchangeable active metal cations enhances the dispersion stability of the active components on the support and ensures tight bonding with the support, effectively suppressing the loss of the central active component. This novel approach effectively disperses and fixes the catalytically active components within and on the surface of the support, resulting in a catalyst with excellent dispersion stability. Therefore, based on the special design of the catalyst's composition and structure, this stable state is maintained as much as possible during use, effectively improving the activity stability and extending the service life of the catalyst for the catalytic oxidation of hydrogen chloride to chlorine. The catalyst provided by this invention does not contain toxic components or precious metals, is environmentally friendly, has low preparation costs, and has good prospects for industrial application.

[0042] (2) The catalyst of the present invention does not contain toxic components or precious metals, and is environmentally friendly with low preparation cost.

[0043] (3) The catalyst of the present invention solves the problem of easy volatilization and loss of the active metal center of the catalyst. The Cu loss rate is less than 0.1%, and it has good catalytic activity and stability. Detailed Implementation

[0044] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0045] In one aspect, the present invention provides a catalyst for the catalytic oxidation of hydrogen chloride to chlorine, the catalyst comprising a molecular sieve and an active component supported on the molecular sieve;

[0046] The active components include oxides and / or chlorides of copper, oxides and / or chlorides of auxiliary metals, oxides and / or chlorides of rare earth elements, and oxides and / or chlorides of alkali metals.

[0047] The auxiliary metal is one or more metals selected from Group VIIB, Group VIII, Group IIB, Group IVB, Group IIA, and Group VB.

[0048] Relative to the total weight of the catalyst, the content of copper, calculated as oxides, is 1-20 wt%, preferably 5-16 wt%, more preferably 6-14 wt%; the content of auxiliary metals is 0.1-10 wt%, preferably 0.1-5 wt%, more preferably 0.1-1.5 wt%; the content of rare earth elements is 0.1-13 wt%, preferably 3-10 wt%, more preferably 4.5-10 wt%; and the content of alkali metals is 0.1-10 wt%, preferably 1-8 wt%, more preferably 2-5 wt%.

[0049] Specifically, relative to the total weight of the catalyst, the copper content, calculated as oxides, can be 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, or 20 wt%, etc.; the content of auxiliary metals can be 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, etc. The content of rare earth elements can be 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, or 13wt%, etc.; the content of alkali metals can be 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%, etc. In addition, the aluminum content can be 5-90 wt%, preferably 15-75 wt%, for example, it can be 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt% or 95 wt%, etc.

[0050] In this invention, the content of the molecular sieve is 10-95 wt% relative to the total weight of the catalyst, preferably 20-90 wt%, and more preferably 25-85 wt%.

[0051] In this invention, the content of the molecular sieve is 10-95 wt% relative to the total weight of the catalyst, preferably 20-90 wt%, and more preferably 25-80 wt%.

[0052] In this invention, the active component can be obtained by calcining a mixture containing copper, a fluxing metal, rare earth elements, and an alkali metal, for example, by calcining a soluble salt containing the corresponding element. In the catalyst of this invention, the active component can exist in the form of an oxide and / or a chloride.

[0053] According to the present invention, the auxiliary metal is preferably one or more selected from manganese, cobalt, magnesium, zinc, nickel, titanium, vanadium and chromium, with manganese and / or cobalt being particularly preferred.

[0054] According to the present invention, the rare earth element may be one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium, wherein one or more of lanthanum, cerium, samarium, and praseodymium are preferred.

[0055] According to the present invention, the alkali metal may be sodium and / or potassium, preferably potassium.

[0056] According to the present invention, the molecular sieve can be one or more of X-type molecular sieves, Y-type molecular sieves, and ZSM-5 type molecular sieves, preferably Y-type molecular sieves. Specifically, the Y-type molecular sieve can be one or more of NaY molecular sieves, ultrastable Y-type molecular sieves, NH4Y molecular sieves, HY molecular sieves, and rare earth-containing Y-type molecular sieves.

[0057] A second aspect of the present invention provides a method for preparing a catalyst for the catalytic oxidation of hydrogen chloride to chlorine, the method comprising the following steps:

[0058] (1) Molecular sieve, binder and extrusion aid are dry mixed, and the resulting mixed powder is mixed with adhesive solvent, water and optional first rare earth element salt and then shaped, and then dried and calcined to obtain shaped molecular sieve.

[0059] (2) The shaped molecular sieve obtained in step (1) is impregnated with a mixed solution containing active components, and then the catalyst is obtained by a second drying and a second calcination.

[0060] The mixed solution containing active components contains copper salt, auxiliary metal salt, second rare earth element salt and alkali metal salt.

[0061] The auxiliary metal in the auxiliary metal salt is one or more metals selected from Group VIIB, Group VIII, Group IIB, Group IVB, Group IIA, and Group VB.

[0062] The amounts of the first rare earth element salt, copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt used in the obtained catalyst are such that, relative to the total weight of the catalyst, the content of copper, calculated as oxides, is 1-20 wt%, preferably 5-16 wt%, more preferably 6-14 wt%; the content of the auxiliary metal is 0.1-10 wt%, preferably 0.1-5 wt%, more preferably 0.1-1.5 wt%; the content of the rare earth element is 0.1-13 wt%, preferably 3-10 wt%, more preferably 4.5-10 wt%; and the content of the alkali metal is 0.1-10 wt%, preferably 1-8 wt%, more preferably 2-5 wt%.

[0063] In step (1), the molecular sieve is prepared into the desired shape and size.

[0064] According to the present invention, in step (1), the molecular sieve used can be one or more of X-type molecular sieves, Y-type molecular sieves, and ZSM-5 type molecular sieves, preferably Y-type molecular sieves. Specifically, the Y-type molecular sieve can be one or more of NaY molecular sieves, ultrastable Y-type molecular sieves, NH4Y molecular sieves, HY molecular sieves, and rare earth-containing Y-type molecular sieves. The silica-alumina ratio of the molecular sieve is preferably 2-60, more preferably 5-30.

[0065] According to the present invention, the binder is preferably an aluminum-containing binder and / or a silicon-containing binder, such as alumina, boehmite, silica sol, aluminum sol, etc. The weight ratio of molecular sieve to binder can be, for example, 10:1 to 1:10, preferably 1-10:1.

[0066] According to a preferred embodiment of the present invention, the mixed powder used for molding may also contain extrusion aids, pore-forming agents, adhesives, and other auxiliary components as needed. The extrusion aid may be guar gum powder, starch, hydroxypropyl methylcellulose, sodium hydroxymethylcellulose, polyethylene glycol, glycerol, etc., with guar gum powder being the most preferred. The amount of extrusion aid relative to the total weight of the mixed powder may be 0.5-5 wt%, preferably 1-3 wt%.

[0067] The amount of molecular sieve is 10-95 wt%, preferably 20-90%, relative to the total weight of the final catalyst. Furthermore, the aluminum content, calculated as alumina, is 5-90 wt%, preferably 15-70 wt%, relative to the total weight of the final catalyst.

[0068] In step (1), the method of dry mixing is not particularly limited; for example, a mixer commonly used for catalyst preparation can be used. Preferably, the dry mixing time is 20 minutes or more, for example, 20-120 minutes. Through dry mixing, the molecular sieve, binder, extrusion aid, and other components can be thoroughly mixed.

[0069] In step (1), the adhesive solvent can be any of the various adhesive solvents commonly used for molecular sieve molding, such as a solution of one or more of nitric acid, hydrochloric acid, and phosphoric acid. The preferred concentration of the adhesive solvent is 0.1-65 wt%, more preferably 2.5-20 wt%. The amount of adhesive solvent solution used relative to 1 part by weight of the mixed powder can be 0.3-0.85 mL, preferably 0.6-0.8 mL.

[0070] In step (1), optionally, when the first rare earth element salt is added, when the mixed powder is mixed with the peptide, water and the first rare earth element salt, a mixed solution containing the peptide and the first rare earth element salt can be added, or the peptide solution and the first rare earth element salt solution can be added separately.

[0071] In step (1), the molding method is not particularly limited, as long as the desired shape and size of the molded molecular sieve can be obtained. For example, extrusion molding, ball rolling molding, compression molding, etc. can be used. The final molded molecular sieve shape can be, for example, strip-shaped, toothed spherical, clover-shaped, four-leaf clover-shaped, or other irregular shapes. Furthermore, the kneading time for molding is preferably 30-180 min, more preferably 30-120 min.

[0072] In step (1), the conditions for the first drying are not particularly limited. For example, drying can be done at room temperature or at 60-120°C for 1-12 hours. The conditions for the first calcination may include: a calcination temperature of 400-650°C, preferably 420-550°C, and a calcination time of 1-6 hours, preferably 2.5-5 hours.

[0073] According to some preferred embodiments of the present invention, the method further includes: contacting the shaped molecular sieve obtained in step (1) with an ammonium acid solution, and then performing the impregnation step (2), wherein the ammonium acid solution contains an acid and an ammonium salt.

[0074] In the ammonium acid solution, the acid can be an organic acid or an inorganic acid. Specifically, the acid can be one or more of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, oxalic acid, and citric acid, and the ammonium salt can be one or more of ammonium nitrate, ammonium sulfate, and ammonium chloride. Furthermore, the molar ratio of acid to ammonium salt in the ammonium acid solution is 1:1-100, preferably 1:10-50. In addition, the concentration of acid can be 0.01-0.1 mol / L, preferably 0.01-0.05 mol / L; the concentration of ammonium salt can be 0.1-1 mol / L, preferably 0.2-0.5 mol / L.

[0075] Furthermore, before contacting the ammonium acid solution, it is preferable to wash the shaped molecular sieve obtained in step (1); after contacting the ammonium acid solution, it is preferable to further wash, dry, and optionally calcine. The drying temperature can be 25-120℃, preferably 60-90℃, and the time can be 1-6 hours, preferably 2-4 hours. The calcination temperature can be 400-600℃, preferably 420-550℃, and the time can be 1-6 hours, preferably 2-4 hours.

[0076] In this invention, step (2) involves loading the active component onto a molded molecular sieve to obtain the catalyst of this invention. Specifically, the loading is performed by impregnating the molded molecular sieve with a mixed solution containing the active component. The mixed solution containing the active component contains copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt, and all of the above salts are soluble salts.

[0077] According to the present invention, copper salts can be copper chloride, copper nitrate, etc.

[0078] According to the present invention, the auxiliary metal in the auxiliary metal salt is one or more of Group VIIB, Group VIII, Group IIB, Group IVB, Group IIA, and Group VB metals, preferably one or more of manganese, cobalt, magnesium, zinc, nickel, titanium, vanadium, and chromium, and more preferably one or more of manganese, cobalt, magnesium, zinc, and nickel.

[0079] According to the present invention, the rare earth elements in the first rare earth element salt and the second rare earth element salt are each independently one or more selected from lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium, preferably one or more selected from lanthanum, cerium, praseodymium, and neodymium. Furthermore, the first rare earth element salt and the second rare earth element salt may be the same or different. The first rare earth element salt and the second rare earth element salt may be nitrates, chlorides, etc., such as lanthanum chloride, cerium chloride, samarium chloride, praseodymium chloride, lanthanum nitrate, cerium nitrate, samarium nitrate, praseodymium nitrate, etc.

[0080] According to the present invention, the alkali metal in the alkali metal salt is sodium and / or potassium, preferably potassium. Examples of the alkali metal salt may be potassium chloride, potassium nitrate, potassium acetate, etc.

[0081] According to the present invention, in step (2), the impregnation is sufficient to achieve the effect of loading the active component. The impregnation is preferably atmospheric pressure impregnation, vacuum impregnation or pressure impregnation at 0-99°C, more preferably vacuum impregnation, and the impregnation time is 0.1-12h, preferably 0.5-6h.

[0082] According to the present invention, in step (2), the conditions for the second drying may include: a drying temperature of 60-120°C, preferably 80-110°C, and a drying time of 2-12h, preferably 6-12h.

[0083] According to the present invention, in step (2), the conditions for the second calcination may include: under an oxygen-containing atmosphere, the calcination temperature is 400-600℃, preferably 450-550℃, and the calcination time is 2-8h, preferably 4-6h.

[0084] According to a preferred embodiment of the present invention, the preparation method includes the following steps:

[0085] (1) Weigh each powder material, and dry mix the molecular sieve, binder and extrusion aid for more than 20 minutes to obtain mixed powder;

[0086] (2) Prepare a solution of adhesive solvent and optional rare earth element salt, spray the solution evenly onto the mixed powder and roll it, and then shape it after rolling.

[0087] (3) The molecular sieves formed into a specific shape are dried and calcined to obtain the shaped molecular sieves;

[0088] (4) The shaped molecular sieve from step (3) is further washed, and then contacted with a certain amount of ammonium acid solution at room temperature and pressure for 0-3 times. After filtration and separation, it is washed, dried, and optionally calcined.

[0089] (5) Dissolve each catalytic active component salt (copper salt, auxiliary metal salt, rare earth element salt, alkali metal salt) in an appropriate amount of water, and then add the solution containing the metal element of the catalytic active component to the product of step (4) or the molecular sieve product formed in step (3) for exchange impregnation for 0.1-24h, and then dry and calcinate to obtain the catalyst product.

[0090] The third aspect of the present invention provides the application of the copper-based catalyst of the present invention or the copper-based catalyst obtained by the preparation method of the present invention in the catalytic oxidation of hydrogen chloride to produce chlorine.

[0091] A fourth aspect of the present invention provides a method for preparing chlorine gas, the method comprising: contacting hydrogen chloride with oxygen in the presence of a catalyst;

[0092] The catalyst is either the copper-based catalyst of the present invention or a copper-based catalyst obtained by the preparation method of the present invention.

[0093] Preferably, the conditions for the contact reaction include: a temperature of 350-390°C, a pressure of 0-0.5 MPa, and a molar ratio of hydrogen chloride to oxygen of 8-0.5:1; more preferably, a temperature of 360-380°C, a pressure of 0-0.3 MPa, and a molar ratio of hydrogen chloride to oxygen of 6-0.5:1.

[0094] By using the catalyst of this invention, the Cu loss rate can be reduced to less than 0.1%.

[0095] The present invention will be described in detail below through examples. In the following examples, the ultrastable Y molecular sieve (ultrastable Y-1: DASY-0.0, ultrastable Y-2: DASY-2.0), NaY molecular sieve, HY molecular sieve, NH4Y molecular sieve, X molecular sieve and ZSM-5 molecular sieve were all produced by Sinopec Catalyst Co., Ltd. Qilu Branch.

[0096] Example 1 (CuMnLaK-Ultrastable Y-1)

[0097] Weigh out ultrastable Y molecular sieve (ultrastable Y-1), alumina powder, and guar gum powder, wherein the mass ratio of ultrastable Y molecular sieve to alumina powder is 4:1, and the weight of guar gum powder is 2.5% of the total powder weight. Add them sequentially to a mixer and dry mix for 120 min. Then, spray 5 wt% nitric acid solution (75 mL / 100 g mixed powder) evenly onto the powder and knead it. After kneading for 30 min, start extruding the molecular sieve strips. Place the extruded molecular sieve strips at 60℃ for 12 h and then calcine them at 550℃ for 6 h to obtain the shaped molecular sieve.

[0098] Weigh out copper chloride, manganese chloride, lanthanum chloride, and potassium chloride (15g of copper chloride, with a Cu:Mn:La:K weight ratio of 1:0.05:0.42:0.22 as oxides), dissolve in water to form a mixed solution containing the active components (Cu... 2+ The concentration is 3M. ​​Then, 50g of molded molecular sieve strips are added to the mixed solution and the two are mixed and impregnated for 12h. Then, it is dried at 110℃ for 12h and then calcined at 450℃ for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0099] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 13.6 wt% copper, 0.5 wt% manganese, 6.8 wt% lanthanum, and 2.8 wt% potassium.

[0100] Example 2 (CuMnLaK-NaY)

[0101] Weigh out NaY molecular sieve, alumina powder, and guar gum powder, wherein the mass ratio of NaY molecular sieve to alumina powder is 3:1, and the weight of guar gum powder is 2.5% of the total powder weight. Add them sequentially to a mixer and dry mix for 120 min. Then, spray a 5 wt% nitric acid solution (80 mL / 100 g mixed powder) evenly onto the powder and knead it. After kneading for 30 min, start extruding the molecular sieve strips. Place the extruded molecular sieve strips at 60℃ for 12 h and then calcine them at 550℃ for 6 h to obtain the shaped molecular sieve.

[0102] Weigh out copper chloride, manganese chloride, lanthanum chloride, and potassium chloride (15g of copper chloride, with Cu:Mn:La:K ratio of 1:0.04:0.35:0.15 as oxides) and dissolve them in water to form a mixed solution containing active components. Then add 50g of molded molecular sieve strips to the mixed solution and impregnate them for 12h. Then dry them at 110℃ for 12h and calcine them at 450℃ for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0103] Relative to the total mass of the catalyst product, the catalyst product contains 13.7 wt% copper, 0.4 wt% manganese, 6.5 wt% lanthanum, and 2.3 wt% potassium, in terms of oxides.

[0104] Example 3 (CuMnLaK-NH4Y)

[0105] Weigh out NH4Y molecular sieve, alumina powder, and guar gum powder, wherein the mass ratio of NH4Y molecular sieve to alumina powder is 4:1, and the weight of guar gum powder is 2.5% of the total powder weight. Add them sequentially to a mixer and dry mix for 120 min. Then, spray a 5 wt% nitric acid solution (70 mL / 100 g mixed powder) evenly onto the powder and knead it. After kneading for 30 min, start extruding the molecular sieve strips. Place the extruded molecular sieve strips at 60℃ for 12 h and then calcine them at 550℃ for 6 h to obtain the shaped molecular sieve.

[0106] Weigh out copper chloride, manganese chloride, lanthanum chloride, and potassium chloride (15g of copper chloride, with Cu:Mn:La:K ratio of 1:0.10:0.35:0.25 as oxides) and dissolve them in water to form a mixed solution containing active components. Then add 50g of molded molecular sieve strips to the mixed solution and impregnate them for 12h. Then dry them at 110℃ for 12h and calcine them at 450℃ for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0107] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 13.6 wt% copper, 0.9 wt% manganese, 6.6 wt% lanthanum, and 3.2 wt% potassium.

[0108] Example 4 (CuMnLaK-HY)

[0109] Weigh out HY molecular sieve, alumina powder, and guar gum powder, with the mass ratio of HY molecular sieve to alumina powder being 4:1 and the weight of guar gum powder being 2.5% of the total powder weight. Add them sequentially to a mixer and dry mix for 120 min. Then, spray a 5 wt% nitric acid solution (65 mL / 100 g mixed powder) evenly onto the powder and knead it. After kneading for 30 min, start extruding the molecular sieve strips. Place the extruded molecular sieve strips at 60℃ for 12 h and then calcine them at 550℃ for 6 h to obtain the shaped molecular sieve.

[0110] Weigh out copper chloride, manganese chloride, lanthanum chloride, and potassium chloride (15g of copper chloride, with Cu:Mn:La:K ratio of 1:0.05:0.46:0.25 as oxides) and dissolve them in water to form a mixed solution containing active components. Then add 50g of molded molecular sieve strips to the mixed solution and impregnate them for 12h. Then dry them at 110℃ for 12h and calcine them at 450℃ for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0111] Relative to the total mass of the catalyst product, the catalyst product contains 13.2 wt% copper, 0.5 wt% manganese, 6.7 wt% lanthanum, and 3.1 wt% potassium, in terms of oxides.

[0112] Example 5 (CuCoLaK-Ultra-stable Y-1)

[0113] The catalyst product was prepared according to the method of Example 1, except that copper chloride, cobalt chloride, lanthanum chloride, and potassium chloride (15g of copper chloride, with Cu:Co:La:K ratio of 1:0.04:0.42:0.22 as oxides) were weighed and dissolved in water to form a mixed solution containing active components.

[0114] Relative to the total mass of the catalyst product, the catalyst product contains 13.6 wt% copper, 0.5 wt% cobalt, 6.8 wt% lanthanum, and 2.8 wt% potassium, in terms of oxides.

[0115] Example 6 (CuNiCeK-Ultrastable Y-1)

[0116] The catalyst product was prepared according to the method of Example 1, except that copper chloride, nickel chloride, cerium chloride, and potassium chloride (15g of copper chloride, with Cu:Ni:Ce:K ratio of 1:0.03:0.44:0.24 as oxides) were weighed and dissolved in water to form a mixed solution containing active components.

[0117] Relative to the total mass of the catalyst product, the catalyst product contains 13.6 wt% copper, 0.4 wt% nickel, 6.8 wt% cerium, and 2.8 wt% potassium, in terms of oxides.

[0118] Example 7 (CuMgCeK-ultrastable Y-1)

[0119] The catalyst product was prepared according to the method of Example 1, except that copper chloride, magnesium chloride, cerium chloride, and potassium chloride (15g of copper chloride, with Cu:Mg:Ce:K ratio of 1:0.04:0.45:0.25 as oxides) were weighed and dissolved in water to form a mixed solution containing active components.

[0120] Relative to the total mass of the catalyst product, the catalyst product contains 13.6 wt% copper, 0.4 wt% magnesium, 6.8 wt% cerium, and 2.8 wt% potassium, in terms of oxides.

[0121] Example 8 (CuMnSmK-Ultra-stable Y-1)

[0122] The catalyst product was prepared according to the method of Example 1, except that copper chloride, manganese chloride, samarium chloride, and potassium chloride (15g of copper chloride, with Cu:Mn:Sm:K ratio of 1:0.05:0.43:0.23 as oxides) were weighed and dissolved in water to form a mixed solution containing active components.

[0123] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 13.6 wt% copper, 0.5 wt% manganese, 6.8 wt% samarium, and 2.9 wt% potassium.

[0124] Example 9 (CuMnPrK-Ultrastable Y-1)

[0125] The catalyst product was prepared according to the method of Example 1, except that copper chloride, manganese chloride, praseodymium chloride, and potassium chloride (15g of copper chloride, and the ratio of Cu:Mn:Pr:K as oxides is 1:0.05:0.42:0.25) were weighed and dissolved in water to form a mixed solution containing active components.

[0126] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 13.6 wt% copper, 0.5 wt% manganese, 6.6 wt% praseodymium, and 3.0 wt% potassium.

[0127] Example 10 (CuMnLaSmK-Ultrastable Y-1)

[0128] Weigh out ultrastable Y molecular sieve, alumina powder, and guar gum powder, wherein the mass ratio of ultrastable Y molecular sieve to alumina powder is 4:1, and the weight of guar gum powder is 2.5% of the total powder weight. Add them sequentially to a mixer and dry mix for 120 min. Then, a solution containing nitric acid and lanthanum chloride (75 mL / 100 g mixed powder, nitric acid concentration of 5 wt%, and mass ratio of ultrastable Y molecular sieve to lanthanum (calculated as oxide) of 8:1) is evenly sprayed onto the powder and kneaded. After kneading for 30 min, extrusion is started. The extruded molecular sieve strips are dried at 60℃ for 12 h, and then calcined at 550℃ for 6 h to obtain the shaped molecular sieve.

[0129] Weigh out copper chloride, manganese chloride, samarium chloride, and potassium chloride (15g of copper chloride, with Cu:Mn:Sm:K ratio of 1:0.05:0.38:0.22 as oxides) and dissolve them in water to form a mixed solution containing active components. Then add 50g of molded molecular sieve strips to the mixed solution and impregnate them for 12h. Then dry them at 110℃ for 12h and calcine them at 450℃ for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0130] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 12.8 wt% copper, 0.4 wt% manganese, 2.5 wt% lanthanum, 6.2 wt% samarium, and 2.6 wt% potassium.

[0131] Example 11 (CuMnLaSmK-Ultrastable Y-2)

[0132] The catalyst product was prepared according to the method of Example 1, except that copper chloride, manganese chloride, lanthanum chloride, samarium chloride, and potassium chloride (15g of copper chloride, with Cu:Mn:La:Sm:K ratio of 1:0.05:0.20:0.21:0.22 as oxides) were weighed and dissolved in water to form a mixed solution containing active components.

[0133] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 13.6 wt% copper, 0.5 wt% manganese, 3.3 wt% lanthanum, 3.6 wt% samarium, and 2.9 wt% potassium.

[0134] Example 12 (CuMnLaK-X)

[0135] The catalyst product was prepared according to the method of Example 1, except that X molecular sieve was used instead of ultrastable Y molecular sieve.

[0136] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 12.5 wt% copper, 0.3 wt% manganese, 6.3 wt% lanthanum, and 2.9 wt% potassium.

[0137] Example 13 (CuMnLaK-ZSM-5)

[0138] Weigh out ZSM-5 molecular sieve, alumina powder, and guar gum powder, wherein the mass ratio of ZSM-5 molecular sieve to alumina powder is 4:1, and the weight of guar gum powder is 2.5% of the total powder weight. Add them sequentially to a mixer and dry mix for 120 min. Then, spray a 5 wt% nitric acid solution (75 mL / 100 g mixed powder) evenly onto the powder and knead it. After kneading for 30 min, start extruding the molecular sieve strips. Dry the extruded molecular sieve strips at 60℃ for 12 h, and then calcine them at 550℃ for 6 h to obtain the shaped molecular sieve.

[0139] Weigh out copper chloride, manganese chloride, lanthanum chloride, and potassium chloride (15g of copper chloride, with Cu:Mn:La:K ratio of 1:0.10:0.40:0.25 as oxides) and dissolve them in water to form a mixed solution containing active components. Then add 50g of molded molecular sieve strips to the mixed solution and impregnate them for 12h. Then dry them at 110℃ for 12h and calcine them at 450℃ for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0140] Relative to the total mass of the catalyst product, the catalyst product contains, in terms of oxides, 10.9 wt% copper, 0.9 wt% manganese, 4.9 wt% lanthanum, and 3.2 wt% potassium.

[0141] Example 14 (CuMnLaK-Ultrastable Y-1)

[0142] The catalyst product was prepared according to the method of Example 1, except that the shaped molecular sieve was modified by contacting it with a mixed solution of ammonium acid (containing 0.01M hydrochloric acid and 0.5M ammonium chloride) at a liquid-to-solid ratio of 10:1, then filtered and separated, dried at 80°C for 6 hours, calcined at 500°C for 4 hours, and then contacted with a mixed solution containing active components to finally obtain the catalyst.

[0143] Relative to the total mass of the catalyst product, the catalyst product contains 13.6 wt% copper, 0.6 wt% manganese, 6.9 wt% lanthanum, and 2.8 wt% potassium, in terms of oxides.

[0144] Comparative Example 1 (CuLaK-Superstable Y-1)

[0145] The copper-based catalyst was prepared according to the method in Example 1, except that the mixed solution containing the active components did not contain the auxiliary metal component (manganese chloride). Specifically, copper chloride, lanthanum chloride, and potassium chloride (15g of copper chloride, with a Cu:La:K ratio of 1:0.42:0.22 based on oxides) were weighed and dissolved in water to form a mixed solution containing the active components. Then, 50g of shaped molecular sieve strips were added to the mixed solution, allowing them to mix and impregnate for 12 hours. The mixture was then dried at 110°C for 12 hours and calcined at 450°C for 6 hours in an oxygen-containing atmosphere to obtain the catalyst product.

[0146] Relative to the total mass of the catalyst product, the catalyst product contains 13.6 wt% copper, 6.8 wt% lanthanum, and 2.8 wt% potassium, in terms of oxides.

[0147] Comparative Example 2 (CuMnK-Ultra-stable Y-1)

[0148] The catalyst was prepared according to the method of Example 1, except that the mixed solution containing the active components did not contain rare earth element components (lanthanum chloride). Specifically, copper chloride, manganese chloride, and potassium chloride (15g of copper chloride, with a Cu:Mn:K ratio of 1:0.05:0.22 based on oxides) were weighed and dissolved in water to form a mixed solution containing the active components. Then, 50g of shaped molecular sieve strips were added to the mixed solution, and the two were mixed and impregnated for 12h. The mixture was then dried at 110°C for 12h, and then calcined at 450°C for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0149] Relative to the total mass of the catalyst product, the catalyst product contains 14.0 wt% copper, 1.2 wt% manganese, and 3.0 wt% potassium, in terms of oxides.

[0150] Comparative Example 3 (CuMnLa-Ultra-Stable Y-1)

[0151] The catalyst was prepared according to the method of Example 1, except that the mixed solution containing the active components did not contain the alkali metal element component (potassium chloride). Specifically, copper chloride, manganese chloride, and lanthanum chloride (15g of copper chloride, with a Cu:Mn:La ratio of 1:0.05:0.42 based on oxides) were weighed and dissolved in water to form a mixed solution containing the active components. Then, 50g of shaped molecular sieve strips were added to the mixed solution, and the two were mixed and impregnated for 12h. The mixture was then dried at 110°C for 12h, and then calcined at 450°C for 6h in an oxygen-containing atmosphere to obtain the catalyst product.

[0152] Relative to the total mass of the catalyst product, the catalyst product contains 13.6 wt% copper, 0.5 wt% manganese, and 6.8 wt% lanthanum, in terms of oxides.

[0153] Comparative Example 4 (CuMnLaK-Al2O3)

[0154] Commercially available shaped alumina (spherical activated alumina from Zibo Haiming Aluminum Co., Ltd.) was selected as the carrier. A mixed solution containing the active components was formed using the same amount and ratio of active components as in Example 1. Then, 50g of shaped alumina was added to the mixed solution, and the two were mixed and impregnated for 12h. The solution was then dried at 110°C for 12h and then calcined at 450°C for 6h in an oxygen-containing atmosphere to obtain the supported catalyst product prepared by conventional methods.

[0155] Relative to the total mass of the catalyst product, the catalyst product contains 12.6 wt% copper, 0.4 wt% manganese, 4.8 wt% lanthanum, and 2.2 wt% potassium, in terms of oxides.

[0156] Test case

[0157] The above-mentioned catalyst was used for the catalytic oxidation of hydrogen chloride to produce chlorine. Specifically, the prepared catalyst was crushed into 40-60 mesh particles, and 2.5 g of the prepared catalyst was weighed and loaded into a small fixed-bed reactor. Hydrogen chloride and oxygen were then introduced into the fixed-bed reactor at rates of 57.6 mL / min and 38.4 mL / min, respectively (HCl / O2 = 1.5:1). The reaction was carried out at a temperature of 370℃ and a pressure of 0.1 MPa. The HCl conversion results after 2 hours and 24 hours of continuous reaction are shown in Table 1.

[0158] The method for determining the HCl conversion rate is as follows.

[0159] 1. Analytical Methods

[0160] The reactor outlet gas contains chlorine, a small amount of water vapor, oxygen, and unreacted hydrogen chloride. The concentrations of chlorine and hydrogen chloride in these gases need to be analyzed to determine the conversion rate of hydrogen chloride, and subsequently to investigate the catalyst's activity and reaction conditions. The iodometric method is chosen for determining chlorine; when chlorine is passed into a KI solution, it produces I₂. - Then titrate with sodium thiosulfate standard solution. A small amount of hydrogen chloride will also be absorbed into the KI solution, requiring the amount of NaOH standard solution (HCl). The specific steps are as follows:

[0161] (1) Take an appropriate amount of analytical solution into an Erlenmeyer flask and add three drops of 1% starch indicator. The solution will turn blue at this time.

[0162] (2) After stirring, titration was performed with 0.1 mol / L Na2S2O3 standard solution. The following chemical reaction occurred in the conical flask during the titration process.

[0163] (3) When I2 reacts with Na2S2O3, the solution immediately changes from dark blue to colorless and transparent, indicating the titration endpoint has been reached. Record the initial reading V1 (mL) and the final reading V2 (mL) of the burette.

[0164] I₂ + 2Na₂S₂O₃ → 2NaI + Na₂S₄O₆

[0165] After the iodometric titration, the HCl content in the KI solution was determined by titrating with NaOH standard solution using the acid-base neutralization method.

[0166] (1) Add three drops of 1% phenolphthalein indicator to the conical flask after the iodometric titration has been completed, and keep the solution colorless and transparent;

[0167] (2) After stirring with a glass rod, titration was performed with a 0.1 mol / L NaOH standard solution. The following chemical reaction occurred during the titration process.

[0168] (3) When the solution changes from colorless and transparent to light red immediately, the titration endpoint is reached. Record the initial reading V3 (mL) and the final reading V4 (mL) of the burette.

[0169] NaOH + HCl → NaCl + H₂O

[0170] Calculation method

[0171] Based on the titration analysis data, the amounts of Cl2 and HCl, and the conversion rate of HCl were further calculated using the following formulas:

[0172] Amount of Cl2:

[0173] Amount of HCl:

[0174] Conversion rate of HCl:

[0175] The elemental composition of the active components of the catalyst was analyzed by ICP analysis.

[0176] Table 1

[0177] Example 1 86.3% 87.8% Example 2 80.4% 80.5% Example 3 84.2% 84.7% Example 4 86.1% 86.4% Example 5 86.1% 86.2% Example 6 83.6% 83.5% Example 7 84.2% 84.2% Example 8 86.5% 86.9% Example 9 87.0% 87.3% Example 10 87.8% 88.2% Example 11 88.1% 88.4% Example 12 82.9% 83.1% Example 13 83.5% 83.7% Example 14 88.9% 89.1% Comparative Example 1 77.8% 72.3% Comparative Example 2 64.7% 56.9% Comparative Example 3 69.2% 62.4% Comparative Example 4 80.1% 74.9%

[0178] As can be seen from the results in Table 1, Examples 1-14 using the catalyst of the present invention have higher HCl conversion rates.

[0179] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A catalyst for the catalytic oxidation of hydrogen chloride to chlorine, characterized in that, The catalyst comprises a molecular sieve and an active component supported on the molecular sieve; The active components include oxides and / or chlorides of copper, oxides and / or chlorides of auxiliary metals, oxides and / or chlorides of rare earth elements, and oxides and / or chlorides of alkali metals. Relative to the total weight of the catalyst, the content of copper (based on oxides) is 1-20 wt%; the content of auxiliary metals is 0.1-10 wt%; the content of rare earth elements is 0.1-13 wt%; and the content of alkali metals is 0.1-10 wt%. The auxiliary metal is one or more of manganese, cobalt, magnesium, zinc, nickel, titanium, vanadium and chromium; The catalyst preparation method includes the following steps: (1) Molecular sieve, binder and extrusion aid are dry mixed, and the resulting mixed powder is mixed with adhesive solvent, water and optional first rare earth element salt and then shaped, and then dried and calcined to obtain shaped molecular sieve. (2) The shaped molecular sieve obtained in step (1) is impregnated with a mixed solution containing active components, and then the catalyst is obtained by a second drying and a second calcination. The mixed solution containing active components contains copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt; the method further includes: contacting the shaped molecular sieve obtained in step (1) with an ammonium acid solution, and then performing the impregnation step (2), wherein the ammonium acid solution contains acid and ammonium salt.

2. The catalyst according to claim 1, wherein, Relative to the total weight of the catalyst, the content of copper, in terms of oxides, is 5-16 wt%; the content of auxiliary metals is 0.1-5 wt%; the content of rare earth elements is 3-10 wt%; and the content of alkali metals is 1-8 wt%.

3. The catalyst according to claim 2, wherein, Relative to the total weight of the catalyst, the content of copper, in terms of oxides, is 6-14 wt%; the content of auxiliary metals is 0.1-1.5 wt%; the content of rare earth elements is 4.5-10 wt%; and the content of alkali metals is 2-5 wt%.

4. The catalyst according to claim 1, wherein, The rare earth elements are one or more of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium; And / or, the alkali metal is sodium and / or potassium.

5. The catalyst according to any one of claims 1-4, wherein, The molecular sieve is one or more of X-type molecular sieve, Y-type molecular sieve and ZSM-5 type molecular sieve.

6. The catalyst according to claim 5, wherein, The molecular sieve is a Y-type molecular sieve.

7. The catalyst according to claim 6, wherein, The molecular sieve is one or more of NaY molecular sieve, ultrastable Y-type molecular sieve, NH4Y molecular sieve, HY molecular sieve, and rare earth-containing Y-type molecular sieve.

8. A method for preparing a catalyst for the catalytic oxidation of hydrogen chloride to chlorine, characterized in that, The preparation method includes the following steps: (1) Molecular sieve, binder and extrusion aid are dry mixed, and the resulting mixed powder is mixed with adhesive solvent, water and optional first rare earth element salt and then shaped, and then dried and calcined to obtain shaped molecular sieve. (2) The shaped molecular sieve obtained in step (1) is impregnated with a mixed solution containing active components, and then the catalyst is obtained by a second drying and a second calcination. The mixed solution containing active components contains copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt. The auxiliary metal in the auxiliary metal salt is one or more of manganese, cobalt, magnesium, zinc, nickel, titanium, vanadium and chromium; The amounts of the first rare earth element salt, copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt used in the obtained catalyst are such that, relative to the total weight of the catalyst, the content of copper (based on oxides) is 1-20 wt%; the content of the auxiliary metal is 0.1-10 wt%; the content of the rare earth element is 0.1-13 wt%; and the content of the alkali metal is 0.1-10 wt%. The method further includes: contacting the shaped molecular sieve obtained in step (1) with an ammonium acid solution and then performing the impregnation step (2), wherein the ammonium acid solution contains an acid and an ammonium salt.

9. The preparation method according to claim 8, wherein, The amounts of the first rare earth element salt, copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt used in the catalyst are such that, relative to the total weight of the catalyst, the content of copper (based on oxides) is 5-16 wt%; the content of auxiliary metal is 0.1-5 wt%; the content of rare earth element is 3-10 wt%; and the content of alkali metal is 1-8 wt%.

10. The preparation method according to claim 9, wherein, The amounts of the first rare earth element salt, copper salt, auxiliary metal salt, second rare earth element salt, and alkali metal salt used in the catalyst are such that, relative to the total weight of the catalyst, the content of copper (calculated as oxides) is 6-14 wt%; the content of auxiliary metal is 0.1-1.5 wt%; the content of rare earth element is 4.5-10 wt%; and the content of alkali metal is 2-5 wt%.

11. The preparation method according to claim 8, wherein, In the ammonium acid solution, the acid is one or more of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, oxalic acid, and citric acid, and the ammonium salt is one or more of ammonium nitrate, ammonium sulfate, and ammonium chloride.

12. The preparation method according to claim 8, wherein, The rare earth element in the rare earth element salt is one or more of the following: lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium. And / or, the alkali metal in the alkali metal salt is sodium and / or potassium.

13. The preparation method according to claim 12, wherein, The auxiliary metal in the auxiliary metal salt is one or more of manganese, cobalt, magnesium, zinc, nickel, titanium, vanadium and chromium.

14. The preparation method according to any one of claims 8-13, wherein, In step (1), the molecular sieve is one or more of X-type molecular sieve, Y-type molecular sieve and ZSM-5 type molecular sieve.

15. The preparation method according to claim 14, wherein, In step (1), the molecular sieve is a Y-type molecular sieve.

16. The preparation method according to claim 15, wherein, In step (1), the molecular sieve is one or more of NaY molecular sieve, ultrastable Y-type molecular sieve, NH4Y molecular sieve, HY molecular sieve, and rare earth-containing Y-type molecular sieve.

17. The preparation method according to any one of claims 8-13, wherein, In step (1), the dry mixing time is more than 20 minutes; And / or, in step (1), the gel solvent solution is one or more of nitric acid, hydrochloric acid, and phosphoric acid, with a concentration of 0.1-65 wt%.

18. The preparation method according to any one of claims 8-13, wherein, In step (1), the kneading time for molding is 30-180 min; And / or, in step (1), the first roasting temperature is 400-650℃ and the roasting time is 1-6h.

19. The preparation method according to claim 18, wherein, In step (1), the kneading time for molding is 30-120 min.

20. The preparation method according to any one of claims 8-13, wherein, In step (2), the impregnation is atmospheric pressure impregnation or vacuum impregnation at 0-99℃, and the impregnation temperature is not 0℃.

21. The preparation method according to claim 20, wherein, In step (2), vacuum impregnation is used, and the impregnation time is 0.1-12h.

22. The preparation method according to any one of claims 8-13, wherein, In step (2), the second drying temperature is 60-120℃, and the drying time is 2-12h; And / or, in step (2), the conditions for the second calcination include: calcination temperature of 400-600℃ and calcination time of 2-8h under an oxygen-containing atmosphere.

23. The preparation method according to claim 22, wherein, In step (2), the second drying temperature is 80-110℃ and the drying time is 6-12h; And / or, in step (2), the conditions for the second calcination include: calcination temperature of 450-550℃ and calcination time of 4-6h under an oxygen-containing atmosphere.

24. The use of the catalyst according to any one of claims 1-7 or the catalyst obtained by the preparation method according to any one of claims 8-23 in the catalytic oxidation of hydrogen chloride to produce chlorine.

25. A method for preparing chlorine gas, characterized in that, The preparation method includes: contacting hydrogen chloride with oxygen in the presence of a catalyst; The catalyst is the catalyst according to any one of claims 1-7 or the catalyst obtained by the preparation method according to any one of claims 8-23.

26. The preparation method according to claim 25, wherein, The conditions for the contact reaction include: a temperature of 350-390℃, a pressure of 0.1-0.5MPa, and a molar ratio of hydrogen chloride to oxygen of 8-0.5:1.

Citation Information

Patent Citations

  • Bifunctional catalyst and preparation method and application thereof

    CN101559374A

  • Hydrochloric acid catalyst containing ruthenium and nickel

    CN102271809A

  • Toluene disproportionation and transalkylation two-component catalyst and preparation method thereof

    CN113492016A